Isu Kejahatan Perang dalam Penyelesaian Konflik Azerbaijan-Armenia Memperebutkan Nagorno-Karabakh - Herlan Febriani; Tri Cahyo Utomo; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The conflict between Azerbaijan and Armenia over Nagorno-Karabakh began with territorial disputes. Nagorno-Karabakh has de facto recognition as Azerbaijan territory, but 95% of its population is Armenian. The relations between both countries continued to tense after a ceasefire in 1994. War crimes issue also affected these two states conflict resolution. This research discusses conflict resolution efforts by Azerbaijan and Armenia and the effect of war crimes issue on their conflict resolution efforts from 2006 to 2015 with the Organization for Security and Cooperation in Europe (OSCE) as mediator. This research is carried out by using descriptive-explanative and qualitative method. This study incorporates the framework of Galtung’s triangle conflict theory and conflict resolution concepts to observe the effect of war crimes issue in conflict resolution between Azerbaijan and Armenia. This study found that the war crimes issue which affected the conflict resolution created the unconducive situation for negotiation. Therefore, it is necessary for those parties to build trust and to reaffirm the importance of international law and international humanitarian law enforcement, also putting conscience as the embodiment of a civilized society.